Providing Complete Basic Immunization and Supplementary Food for Infants and Toddlers: Pemberian Imunisasi Dasar Lengkap dan Makanan Tambahan pada Bayi dan Balita - Novelia, Shinta; Tiara Carolin, Bunga (KHD Production, 2023)
One basic immunization type in Indonesia is DPTHBHib immunization, targeting infants or children aged two to eleven months. DPTHBHib immunization must be given to children to avoid Diphtheria, Pertussis, Tetanus, Hepatitis B, and Haemophilus influenzae type b, which can cause death in children. The vaccination was carried out 3 times at 2 months, 3 months, and 4 months. Since the Covid-19 pandemic, the participation of mothers with toddlers has decreased, especially in the Pondok Jaya Village, Cipayung sub-district, Depok City. Therefore, to support the implementation of Immunization by the Government, it is felt necessary to hold community service for Providing Complete Basic Immunization and Supplementary Food to Infants and Toddlers at Posyandu Delima RW 02 Kel Pondok Jaya Kec Cipayung Depok City in 2022. The results of this community service activity were carried out well and appreciated by the local community. As many as 6 mothers who have babies and toddlers attend posyandu activities.